Capital Flows : The Role of Bank and Nonbank Balance Sheets - Hashimoto, Yuko (IMF Working Papers; Working Paper ;, 2019)
This paper assesses the role of bank and nonbank financial institutions' balance sheet foreign exposures and risk management practices in driving capital flow responses to global risk. Using a unique and previously unexplored dataset on domestic and cross border balance sheet positions of financial institutions collected by the IMF, we show that the response of overall capital flows to global risk shocks is associated with the on-balance sheet foreign exposures of nonbanks, but not with that of banks. A possible interpretation is that risk-averse and dynamically optimizing nonbanks reduce their foreign risk exposure when global risk perceptions increase, leading to capital flows, while banks tend to be hedged against these risks off balance sheet. In advanced countries, the findings suggest that nonbank portfolio adjustment to changing risk conditions may take place through derivatives transactions with banks, the hedging practices of which trigger bank related capital flows rather than portfolio flows.